Tingkat Pengetahuan Perokok dan Implikasinya terhadap Status Periodontal - Jumriani; Liasari, Ira; Priyambodo, R. Ardian; Asriawal; Fitri, Andi Nurannisa (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2025)
Smoking remains a common habit in society and is recognized as a major risk factor for periodontal tissue health problems. This study aimed to examine the relationship between smokers' knowledge levels and the incidence of periodontal disease among the community in Tongke-Tongke Village, East Sinjai District, Sinjai Regency. An observational analytic design with a cross-sectional approach was used. A total of 40 respondents were selected through purposive sampling based on predetermined inclusion and exclusion criteria. Data were collected using a questionnaire to assess knowledge levels and a CPITN examination sheet to evaluate periodontal status. Data analysis was conducted using Spearman correlation tests with the help of SPSS software. The results showed that the smokers' knowledge level was categorized as moderate, while the community's periodontal disease status was generally categorized as poor. Statistical testing indicated a significant relationship between smokers' knowledge levels and periodontal disease, with a p-value of 0.023 (p < 0.05). Thus, it can be concluded that there is a relationship between smokers' knowledge levels and periodontal disease status in Tongke-Tongke Village, East Sinjai District, Sinjai Regency.